A list of cages - Roe, Robin (2017)
When Adam Blake lands the best elective ever in his senior year, serving as an aide to the school psychologist, he thinks he's got it made. Sure, it means a lot of sitting around, which isn't easy for a guy with ADHD, but he can't complain, since he gets to spend the period texting all his friends. Then the doctor asks him to track down the troubled freshman who keeps dodging her, and Adam discovers that the boy is Julian -- the foster brother he hasn't seen in five years. Adam is ecstatic to be reunited. At first, Julian seems like the boy he once knew. He's still kindhearted. He still writes stories and loves picture books meant for little kids. But as they spend more time together, Adam realizes that Julian is keeping secrets, like where he hides during the middle of the day, and what's really going on inside his house. Adam is determined to help him, but his involvement could cost both boys their lives
Keywords: Child abuse -- Juvenile fiction; Foster children -- Juvenile fiction; Attention-deficit disorder in adolescence -- Juvenile fiction; Friendship -- Juvenile fiction; Child abuse -- Fiction; High school students -- Fiction; Foster children -- Fiction; Attention-deficit disorder in adolescence -- Fiction; Young adult fiction